Impacts of human development index and climate conditions on prevalence of Blastocystis: A systematic review and meta-analysis - Javanmard, Ehsan; Niyyati, Maryam; Ghasemi, Erfan; Mirjalali, Hamed; Asadzadeh Aghdaei, Hamid; Zali, Mohammad Reza (Acta tropica, 2018)
[Display omitted] •Blastocystis is an enteric protist with wide distribution in regions with poor hygiene.•The meta-analysis showed that socioeconomic situation and climate conditions have effects on the prevalence of Blastocystis.•The analysis showed that ST3 is predominant among human subjects as well as animals in Iran. Blastocystis is a prevalent eukaryotic microorganism that has been frequently reported from the stool samples of human and animals, all over the world. The prevalence of this parasite has close correlation with the climate and hygiene situation of studied populations. For the current study, English and Persian databases were searched for the following terms: “Blastocystis hominis”, “Blastocystis sp.”, “Intestinal Parasites”, “Prevalence” and “Iran”. In order to data analysis and assess the possibility of publication bias, STATA v11 and Begg’s Funnel plot were employed respectively. From 605 searched cases, 86 publications met our criteria for the analysis. The pooled prevalence of Blastocystis was 9.1% (95%CI: 8.2%, 10.1%). The results represented that the prevalence of the parasite using molecular techniques or cultivation followed by molecular techniques (20.89%) was higher than only microscopical examination (8.96%). The prevalence rate of Blastocystis according to human development index was 7.6%, 7.2%, 11.9%, 13.4%, and 3.3% for ranks 1 to 5, respectively. This is the first study signifying the prevalence of Blastocystis regarding the human development index and climate conditions. The findings represented that although human development index, low levels of socioeconomic situations together with appropriate climate such as sufficient humidity and high temperature increase the chance of transmission of Blastocystis in a society.